Implementation of the Process for Contamination in Electromyography (EMG) Signal by Using Noise Removal Techniques - Oo, Nandar; Tun, Hla Myo; Pradhan, Devasis; Win, Lei Lei Yin; Aye, Mya Mya; Oo, Thandar (Journal of Novel Engineering Science and Technology, 2024)
The paper describes the analysis of electromyography (EMG) signals using noise removal techniques. The problem in this study is to consider a noise removal technique for basic EMG signal processing by the Band Pass Filter method. A research approach to designing simulation codes for observing EMG signal modeling and noise removal techniques through mathematical methods from signals and systems concepts. The results confirm that it can provide high-performance target monitoring of the EMG signal in real-world applications.